PENEGAKAN HUKUM TERHADAP OKNUM POLISI YANG MELAKUKAN PELANGGARAN KODE ETIK DALAM MENJALANKAN TUGAS DI WILAYAH HUKUM POLRES SALATIGA JAWA TENGAH (Jurnal De Jure Muhammadiyah Cirebon, 2023)
Background to find out law enforcement against police officers who violate the code of ethics in carrying out their duties in the jurisdiction of the Salatiga Police, obstacles in law enforcement against police officers who violate the code of ethics in carrying out their duties, solutions to overcome obstacles in law enforcement against police officers who violates the code of ethics in carrying out their duties. The results of the research are the legal basis for the Police Professional Code of Ethics, namely Law No. 2 of 2002, Article 13 paragraph (1). The ideal arrangement for resolving violations of the Code of Ethics by members of the Police within the jurisdiction of the Salatiga Police is based on Law Number 2 of 2002, Government Regulation Number 1 of 2003, Government Regulation Number 2 of 2003 and Presidential Regulation Number 52 of 2010. The process of handling Police who violate the police professional code of ethics in committing criminal offenses are basically carried out in accordance with the provisions of the Criminal Procedure Code (KUHAP), and the rules governing POLRI specifically. The obstacles are due to statutory factors (legal substance). Law enforcement factors, infrastructure or facilities factors and legal awareness factors. The steps for implementing the development of Human Resources (HR) in the Salatiga Polres environment through the Development of Human Resources (HR) through education and training, Development of Human Resources (HR) through assignments, through transfers and promotions, through career development, Development of Human Resources (HR) through supervision and control.Keywords: law enforcement; police personnel; violation of the code of ethics